2014
DOI: 10.1080/03057925.2014.930659
|View full text |Cite
|
Sign up to set email alerts
|

Student teachers’ views of practicums (teacher training placements) in Turkish and English contexts: a comparative study

Abstract: How student teachers experience their transformation into serving teachers in the liminal social spaces of the school-based practicum (teaching practice) is of key importance to them, their future students and their educators. The practicum is a challenging experience for student-teachers, even with help from university and school-based mentors, as their knowledge of practice, power and culture in schools lacks sophistication. The practicum, an under-researched but important aspect of education, was investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 59 publications
1
11
1
Order By: Relevance
“…This study also conforms to the previous studies as it was also found out that teaching practicum was the key component of teacher education (Ozmen, 2012;Barton et al, 2015;Tülüce & Çeçen, 2016) and that it promoted personal development and enhanced social responsibility and personal competence (Chambers & Lavery, 2012). The results also indicated similarity as is the case in previous studies as teaching practicum was also effective in pre-service ELT teachers' obtaining e periences about communication, classroom management and understanding students' social and cognitive background (Alaz & Konur, 2009;Busher et al, 2015). The results also showed parallelism and consistency with the study of Sariçoban (2016) as it indicated teaching practicum was helpful for them to develop more positive attitudes towards their profession.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…This study also conforms to the previous studies as it was also found out that teaching practicum was the key component of teacher education (Ozmen, 2012;Barton et al, 2015;Tülüce & Çeçen, 2016) and that it promoted personal development and enhanced social responsibility and personal competence (Chambers & Lavery, 2012). The results also indicated similarity as is the case in previous studies as teaching practicum was also effective in pre-service ELT teachers' obtaining e periences about communication, classroom management and understanding students' social and cognitive background (Alaz & Konur, 2009;Busher et al, 2015). The results also showed parallelism and consistency with the study of Sariçoban (2016) as it indicated teaching practicum was helpful for them to develop more positive attitudes towards their profession.…”
Section: Resultssupporting
confidence: 69%
“…In sum, similarly, the results of the study did not contradict to the results of the previous research in terms of the pre-service teachers' confrontation with many difficulties when their theoretically gained beliefs were confronted with the practically gained reality (Stenberg, Rajala, Hilppo, 2016;Debreli, 2016). The results also did not negate to the previous studies regarding pre-service teachers' appreciating what it means to be a teacher 'for real' and developing their skills (Aydin, Selcuk & Yesilyurt, 2007;Busher et al 2015). Additionally, the results comply with the previous results concerning pre-service teachers' inadequacy in English language competence which appeared to affect their teaching performance (Gan, 2013) and concerning their consideration on what teaching entailed (Morales Cortés, 2016).…”
Section: Resultscontrasting
confidence: 52%
See 1 more Smart Citation
“…The school placement experience (often referred to as the 'Practicum') is long established as a central component of teacher education programmes (MacBeath, 2011;Wilson, Floden, & Ferrini-Mundy, 2001) and is widely acknowledged to be a critical period for the professional growth for student-teachers (Busher, Gündüz, Cakmak, & Lawson, 2015;Fazio & Volante, 2011). Much has been written about what constitutes a 'good' and positive practicum placement (Beck & Kosnik, 2002;Moody, 2009) and indeed, the challenges and stresses that student-teachers can experience during periods of SP (Moos & Pitton, 2014;Murray-Harvey, 2001).…”
Section: School Placement and Belongingmentioning
confidence: 99%
“…TEMAG, 2014). However, while the practicum is generally considered by participants to be one of the most influential experiences in their preservice teacher education (Busher, Gündüz, Cakmak, & Lawson, 2015) it is also recognised as being one of the most stressful (Gardner, 2010). As a result, there is an increasing tendency in recent work to explore the practicum through the eyes and experiences of participants (Buckworth, 2017;GrantSmith & Gillett-Swan, 2017).…”
Section: Editorialmentioning
confidence: 99%